2012
DOI: 10.1155/2012/121878
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Expanding the Reach of Early Autism Training to Parents

Abstract: Although there is consensus that parents should be involved in interventions designed for young children with autism spectrum disorder (ASD), parent participation alone does not ensure consistent, generalized gains in children's development. Barriers such as costly intervention, time-intensive sessions, and family life may prevent parents from using the intervention at home. Telehealth integrates communication technologies to provide health-related services at a distance. A 12 one-hour per week parent interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
237
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(259 citation statements)
references
References 39 publications
12
237
2
8
Order By: Relevance
“…25 Because telehealth can provide research-based ABA treatment to any family with access to the Internet, barriers to providing access to ABA can be reduced, especially for rural and underserved families. There is a rapidly growing literature on the use of telehealth to deliver a range of ASD interventions, [26][27][28][29][30] and future issues regarding the delivery of ABA services via telehealth will need to focus on when to provide services and at what intensity to deliver them in relation to other interventions. These timing and dose issues warrant careful study, as will issues such as the effects of ABA treatment on caregiver stress and parenting and the best ways to ensure generalization of children's and parents' newly learned skills.…”
Section: Discussionmentioning
confidence: 99%
“…25 Because telehealth can provide research-based ABA treatment to any family with access to the Internet, barriers to providing access to ABA can be reduced, especially for rural and underserved families. There is a rapidly growing literature on the use of telehealth to deliver a range of ASD interventions, [26][27][28][29][30] and future issues regarding the delivery of ABA services via telehealth will need to focus on when to provide services and at what intensity to deliver them in relation to other interventions. These timing and dose issues warrant careful study, as will issues such as the effects of ABA treatment on caregiver stress and parenting and the best ways to ensure generalization of children's and parents' newly learned skills.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it was beyond the scope of the review to consider interventions that did not include additional support from a trainer (e.g. those based solely on self-directed learning such as Jang et al 2012), or interventions relating to more broad behavioral methodology rather than defined procedures (e.g., Heitzman-Powell et al 2014;Vismara et al 2009;Vismara et al 2013;Vismara et al 2012); therefore, the utility of telehealth in these contexts cannot be inferred from this review. In addition, due to the nature of systematic review methodology, some relevant articles may not be included if they were not identified as part of the search strategy and it was not possible to include gray literature such as unpublished manuscripts, dissertations, or book chapters.…”
Section: Limitations and Areas For Further Studymentioning
confidence: 99%
“…Although some authors have applied telehealth methodology to more broad training (see, for example, Heitzman-Powell et al 2014;Reese et al 2015;Vismara et al 2009Vismara et al , 2013Vismara et al , 2012Xie et al 2013), an analysis of the factors related to the effectiveness of telehealth for different types of support and with different behavioral targets is warranted. Finally, the motivations and context for adopting telehealth support in ABA services must be considered.…”
Section: Broader Considerations Relating To Telehealthmentioning
confidence: 99%
“…In this sense, support to parents can also be provided remotely by a telehealth approach, a mechanism that enables individuals to receive professional guidance and effective recommendations from a distance (23) and may involve several multimedia platforms from real time video streaming to interactive website and tablet applications that can be effortlessly accessed at any time and location and shared across settings and individuals (24). Current studies implementing telehealth have already demonstrated encouraging results in training professionals and family members in ABA behavior management procedures (25), and successful outcomes in training parents of children with ASD in specific intervention models such as the ESDM (26).…”
Section: Introductionmentioning
confidence: 99%